Mycophenolate mofetil improves renal haemodynamics, microvascular oxygenation, and inflammation in a rat model of supra‐renal aortic clamping‐mediated renal ischaemia reperfusion injury. (February 2017) - Ergin, Bulent; Heger, Michal; Kandil, Asli; Demirci‐Tansel, Cihan; Ince, Can
Summary: Ischaemia/reperfusion (I/R) is one of the main causes of acute kidney injury (AKI), which is characterized by sterile inflammation and oxidative stress. Immune cell activation can provoke overproduction of inflammatory mediators and reactive oxygen species (ROS), leading to perturbation of the microcirculation and tissue oxygenation associated with local and remote tissue injury. This study investigated whether the clinically employed immunosuppressant mycophenolate mofetil (MMF) was able to reduce I/R‐induced renal oxygenation defects and oxidative stress by preventing sterile inflammation. Rats were divided into three groups (n=6/group): (1) a sham‐operated control group; (2) a group subjected to renal I/R alone (I/R); and (3) a group subjected to I/R and MMF treatment (20 mg/kg prior to I/R) (I/R+MMF). Ischaemia was induced by a vascular occluder placed on the abdominal aorta for 30 minutes, followed by 120 minutes of reperfusion. Renal I/R deteriorated renal oxygenation ( P <.001) and oxygen delivery ( P <.01), reduced creatinine clearance ( P <.01) and tubular sodium reabsorption ( P <.001), and increased iNOS, renal tissue injury markers ( P <.001), and IL‐6 ( P <.001). Oral MMF administration prior to insult restored renal cortical oxygenation ( P <.05) and iNOS, renal injury markers, and inflammation parameters ( P <.001) to near‐baseline levels without affecting renal function. MMF exerted a prophylactic effect on renal microvascular oxygenation and abrogated tissue inflammation and renal injury following lower body I/R‐induced AKI. These findings may have clinical implications during major vascular or renal transplant surgery.